Lisbon five years later. What future for European employment and growth? - Pissarides, Christopher A. (London, 2006)
"At the Lisbon summit of 2000 the European Union (EU) set an agenda for making Europe the most competitive economy in the world. The targets that were set then are unlikely to be achieved. European countries need to concentrate on change in the lower productivity, more labour-intensive service sectors of the economy to improve their poor employment performance. "